2018
DOI: 10.5194/os-2018-148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can wave coupling improve operational regional ocean forecasts for the North-West European Shelf?

Abstract: Operational ocean forecasts are typically produced by modelling systems run using a forced mode approach. The evolution of the ocean state is not directly influenced by surface waves, and the ocean dynamics are driven by an external source of meteorological data which is independent of the ocean state. Model coupling provides one approach to increase the extent to which ocean forecast systems can represent the interactions and feedbacks between ocean, waves and the atmosphere seen in 15 nature. This paper demo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…This work follows that of Lewis et al. (2019), who showed that model coupling alone is not a sufficient strategy for improving all aspects of model performance. The 3DVAR scheme is implemented with the assumption that the model SST errors are strongly correlated with the temperature errors inside the mixing layer.…”
Section: Discussionsupporting
confidence: 63%
“…This work follows that of Lewis et al. (2019), who showed that model coupling alone is not a sufficient strategy for improving all aspects of model performance. The 3DVAR scheme is implemented with the assumption that the model SST errors are strongly correlated with the temperature errors inside the mixing layer.…”
Section: Discussionsupporting
confidence: 63%
“…The AMM15 system described in this paper has been already tested in an ocean-wave coupled configuration (Lewis et al, 2019a) which is planned to become operational in 2020. We hope to add the biogeochemical components in a few years, but a precise plan is not yet available.…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
“…The AMM15 system described in this paper, has been already tested in an ocean-wave coupled configuration (Lewis et al 2018a) which is planned to become operational in 2020. We hope to add the biogeochemical components in a few years, but a precise plan is not yet available.…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
“…The increase of resolution to 1.5 km is therefore a fundamental step change in the ability to resolve key processes and features in the NWS region (Guihou et al, 2017). As well as being developed for ocean forecasting operations, the AMM15 is being used within a coupled ocean-wave-atmosphere research system (Lewis et al, 2018a and.…”
Section: Introductionmentioning
confidence: 99%